QUALITY OF DISTANCE LEARNING IN SECONDARY SCHOOL SPORTS AND HEALTH CLASSES - Teteris, Lūkass Edmunds; Fernāte, Andra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Distance learning or remote studies can break the boundaries of time and space, as students can use computers or electronic devices (for instance, mobile phones and tablets) to instantly acquire learning resources and listen to teachers during remote classes. The pandemic led to procedures that changed the way teachers teach and communicate with students and families. All teachers faced such a situation for the first time, thus it was necessary to invent, acquire and apply new teaching methods in sports and health classes, in order to provide students with the planned amount of physical activity in sports classes, as well as to implement the curriculum. The human body is made for movement; therefore, a person feels best when they move regularly. The aim of this study was to evaluate the skills of sports teachers to apply digital teaching methods in secondary school sports and health classes, and the quality of distance learning. Research methods: the research used surveys, which were issued to 29 secondary schools in Latvia, as well as to 2 respondents from primary schools. In total, 34 respondents filled out the research survey. In order to determine the opinion of sports teachers on the quality of distance learning in sports classes in secondary school and the applied digital skills, interviews were conducted with the participation of 5 sports teachers. Analysing the responses to the survey and the correlations between them, the research results show that if the sports teacher has not acquired digital skills, then online and distance learning cannot be provided, as well as the set learning results in sports in secondary school are not achieved.